New rules for the rationing of the provision of crypto-assets service in light of the MiCA Regulation - Piętka, Jakub (Studia Iuridica Toruniensia, 2025)
The article addresses the issue of changes to the rules for conducting economic activity in the crypto-assets market. The MiCA Regulation has comprehensively regulated the aspects most relevant to the sector, including the requirement to obtain authorisation to operate as a cryptoassets service provider. This necessitates a departure from the current rationing rules under AML/CFT legislation. The purpose of the article is to analyse the new requirements that must be met by entities intending to provide this type of service, compared to the current rationing rules. The article also attempts to identify the implications that the changes introduced may have for business entities and investors placing their funds in crypto-assets.